Hubungan antara Pengetahuan Gizi dan Asupan Zat Imunonutrisi dengan Status Imunitas Pascapandemi Covid-19 pada Mahasiswa Fakultas Kedokteran Universitas Lampung: Association between Nutritional Knowledge and Immunonutrients Intake with Immunity Status Post-Pandemic COVID-19 in College Students - Angraini, Dian Isti; Maulidia, Anisa; Sutarto (Amerta Nutrition, 2024)
Background: The occurrence of COVID-19 pandemic has affected various aspects of life. Several studies have shown that the ability to recover and avoid COVID-19 infection depends on the level of immunity, which is influenced by the intake of immunonutrients. However, healthy eating habits, such as the consumption of these immononutrients, are influenced by a good nutrition understanding. Objectives: This study aimed to determine the association between nutritional knowledge and immunonutrients intake with immunity status post-pandemic COVID-19 in college students. Methods: The study procedures were carried out using an observational analytical method with a cross-sectional design. The sample population comprised 104 first-year students from Medical Education Study Program at Medical Faculty of Lampung University. Students were determined using the unpaired categorical comparative analytics sample size formula and selected with a straightforward simple random sampling method. Data were collected using a questionnaire, including nutritional knowledge, immunonutrients intake, and immune status. Analysis was carried out using Chi-Square test and logistic regression. Results: The result showed that 51.9% of respondents had decreased immunity status. The bivariate test revealed that protein intake (p-value<0.001), zinc (p-value=0.006), iron (p-value<0.001), vitamin A (p-value<0.001), and vitamin C (p-value=0.002) had a relationship with immunity status, while nutritional knowledge (p-value=0.708) had no association. In addition, the factors most related to immunity status were protein, iron, and vitamin C intake. Conclusions: Immunonutrients intake is a factor that directly influenced immunity status, while nutritional knowledge is an indirect factor.